Haemodynamic monitoring in the peri‐operative period: the past, the present and the future. (January 2017) - Watson, X.; Cecconi, M.
Summary: Over recent years there has been an increase in the implementation of goal‐directed therapy using minimally invasive haemodynamic monitoring techniques to guide peri‐operative care. Since the introduction of the pulmonary artery flotation catheter in the 1980s, various haemodynamic monitors have been developed, each associated with their own benefits and limitations. Goal‐directed therapy has been well‐established as a standard of care in the peri‐operative period and has largely been associated with a reduction in morbidity and mortality. However, evidence over the last few years from major studies has led us to question: what is the future for goal‐directed therapy? Care of the peri‐operative patient has significantly evolved over the last decade and this needs to be taken into account when assessing the results of these studies. We should therefore not look at the effects of goal‐directed therapy in isolation but as part of a progressive care bundle. Additionally, other markers of haemodynamic status have also begun to be further appreciated and these are worthy of further investigation. We feel that the future for haemodynamic monitoring remains promising with new areas of interest continuously emerging, but further research is still required.